The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/ajcn/nqaa170
|View full text |Cite
|
Sign up to set email alerts
|

Combined infant and young child feeding with small-quantity lipid-based nutrient supplementation is associated with a reduction in anemia but no changes in anthropometric status of young children from Katanga Province of the Democratic Republic of Congo: a quasi-experimental effectiveness study

Abstract: Background Small-quantity lipid-based nutrient supplements (SQ-LNS) are efficacious in controlled settings; data are scarce on the effectiveness utilizing health care delivery platforms. Objective We evaluated the impact of an infant young child feeding (IYCF)–SQ-LNS intervention on anemia and growth in children aged 6–18 mo in the Democratic Republic of Congo following a quasi-experimental effectiveness design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Thus, further research is needed to investigate potential dose–response relations. In a recent evaluation of a program in the Democratic Republic of Congo in which SQ-LNS was distributed to infants 6–12 mo of age ( 55 ), dose-response was examined among children in the intervention zone who were 8–13 mo of age at endline, who were expected to have sufficient program exposure to expect a biological impact. Within that subsample, and adjusting for multiple potential confounding variables, children who had received ≥3 monthly distributions of SQ-LNS ( n = 80) had significantly greater LAZ (+0.4; 95% CI: 0.02, 0.78) and a lower prevalence of stunting (−16.7 percentage points; 95% CI: −32.1, −1.2 percentage points) than those who did not receive SQ-LNSs ( n = 89), whereas those who received 1–2 monthly distributions of SQ-LNSs ( n = 136) did not differ from those who did not receive SQ-LNSs (LAZ: +0.08; 95% CI: −0.24, 0.41; stunting PD: −9.3; 95% CI: −22.6, 3.9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further research is needed to investigate potential dose–response relations. In a recent evaluation of a program in the Democratic Republic of Congo in which SQ-LNS was distributed to infants 6–12 mo of age ( 55 ), dose-response was examined among children in the intervention zone who were 8–13 mo of age at endline, who were expected to have sufficient program exposure to expect a biological impact. Within that subsample, and adjusting for multiple potential confounding variables, children who had received ≥3 monthly distributions of SQ-LNS ( n = 80) had significantly greater LAZ (+0.4; 95% CI: 0.02, 0.78) and a lower prevalence of stunting (−16.7 percentage points; 95% CI: −32.1, −1.2 percentage points) than those who did not receive SQ-LNSs ( n = 89), whereas those who received 1–2 monthly distributions of SQ-LNSs ( n = 136) did not differ from those who did not receive SQ-LNSs (LAZ: +0.08; 95% CI: −0.24, 0.41; stunting PD: −9.3; 95% CI: −22.6, 3.9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further research is needed to investigate potential dose-response relationships. In a recent evaluation of a program in the Democratic Republic of Congo in which SQ-LNS was distributed to infants 6-12 months of age (52), dose-response was examined among children in the intervention zone who were 8-13 months of age at endline, who were expected to have sufficient program exposure to expect a biological impact. Within that subsample, and adjusting for multiple potential confounding variables, children who had received at least 3 monthly distributions of SQ-LNS (n=80) had significantly greater LAZ (+0.4 (0.02, 0.78)) and a lower prevalence of stunting (−16.7 (−32.1, −1.2) percentage points) compared to those who did not receive SQ-LNS (n=89), whereas those who received 1-2 monthly distributions of SQ-LNS (n=136) did not differ from those who did not receive SQ-LNS (LAZ +0.08 (−0.24, 0.41); stunting prevalence difference −9.3 (−22.6, 3.9)).…”
Section: Discussionmentioning
confidence: 99%
“…Our review identified 15 newer isotopic studies (published alongside their trials registry entries and conference abstracts, since early 2013), which between them addressed absorption, metabolism, balance, body depots and excretion (see Table 2 [ 32 , 36 , 68 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 89 , 90 ], alongside nine older isotopic studies [ 88 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]). The potentially most relevant recent trials explored the effects of multiple nutrient supplementation [ 99 , 100 , 101 , 102 , 103 ], vitamin A supplementation on iron metabolism [ 104 ] or supplementation in conjunction with other treatments [ 105 ]. Older trials assessed the effects of vegetables and green leaves [ 96 , 106 ], milk formula [ 107 ], fortified seasoning powder [ 108 ], micronutrient supplement [ 109 ] and high-dose supplementation [ 110 , 111 , 112 , …”
Section: Resultsmentioning
confidence: 99%